Towards Sustainable Tourism: Impact Evaluation of Green Marketing Strategies and Related Factors: A Systematic Literature Review - Setiadi, Sandi; Widyastuti, Sri; Zulkifli; Darmansyah (GoAcademica Research & Publishing, 2025)
Sustainable tourism has become a major issue affecting the tourism industry in recent years. This study aims to evaluate the impact of green marketing strategies, social media, destination image, and tourists’ perceptions of sustainable tourism practices, with green tourism as a mediating variable. The method used is a systematic literature review with evaluation of reporting quality and methodology based on compliance with the PRISMA checklist and the AMSTAR quality scale. Data were collected from 200 articles categorized into four groups: Group A (15 articles in the last 10 years that explicitly mention PRISMA), Group B (15 articles from the same journal without mentioning PRISMA), Group C (30 articles published a year before the ratification of PRISMA), and Group D (30 articles from 10 journals with the highest impact factors in the field of sustainable tourism that do not support PRISMA). The results of the literature review indicate that green marketing strategies, such as the promotion of environmentally friendly products and services, are able to attract environmentally conscious tourists and encourage sustainable behavior. Social media is also effective in raising awareness and shaping the image of a responsible destination, which in turn influences tourist choice and loyalty. These findings emphasize the need to develop sustainable and environmentally friendly tourism products to optimize economic benefits and environmental preservation in the tourism industry.